Evaluation of compliance of CONSORT-CHM formula 2017 in randomized controlled trials of Chinese herbal medicine formulas: protocol of a five-year review - Wang, Juan; Cheng, Chung Wah; Jiao, Yalin; Shi, Dongni; Wang, Yaochen; Li, Han; Wang, Nana; Wang, Xihong; Li, Yuqin; Liang, Feng; Luo, Shufeng; Han, Fei; et al. (Frontiers in Pharmacology, 2024)
The CONSORT Extension for Chinese Herbal Medicine Formula 2017 (CONSORT-CHM Formula 2017) has established a reporting standard for randomized controlled trials (RCTs) of Chinese Herbal Medicine Formula (CHMF) interventions; however, its adherence and implications for the design and execution of study design remain ambiguous. It is necessary to evaluate the level of compliance with the CONSORT-CHM Formula 2017 in RCTs conducted over the past five years, and to determine the reporting quality of clinical trials in this field.Methods: First, a systematic search is conducted for RCTs on CHMF in EBM Reviews, Allied and Complementary Medicine (AMED), Embase, Ovid-MEDLINE(R), Wanfang data, China National Knowledge Infrastructure (CNKI), VIP Chinese Medical Journal Database (VIP) and Chinese Biomedical Literature (CBM) database, that encompassed CHMF interventional RCTs published from January 1, 2018 to June 8, 2022, with language restriction to English or Chinese. Second, a descriptive analysis will be performed regarding the study design and general characteristics of the included trials. Third, for the quality assessment, we have subdivided the CONSORT-CHM Formula 2017 checklist (consisting of 22 extended items) into a total of 42 subquestions to facilitate scoring, with a specific focus on the description, quality control, and safety assessment of CHMF interventions. Professional training and a pilot test on 100 randomly selected articles will be provided for all reviewers. Throughout this process, a standard operating procedure (SOP) for quality assessment will be developed to ensure consistency. Each item will be assessed by two reviewers in a paired back-toback manner, and the compliance rate will be calculated to assess inter-rater agreement.Discussion: This review will identify the current reporting characteristics and quality of CHMF interventional studies and further evaluate the impact of CONSORT-CHM Formula 2017. The results may provide suggestions for future application or promotion of the guideline.The study has been registered on Open Science Framework (https://osf.io/xpn7f)